Study of reverse planting techniques on rice as physical science learning materials - Hestiana Hestiana; Heru Kuswanto; Aisha Azalia; Desi Ramadhanti (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2021)
The spread of COVID-19 makes learning at every level of the education unit conducted from home online or distance learning. However, this is not an easy thing for teachers to do. Teachers are required to innovate in delivering materials so that students can easily understand and learn actively. Indonesia is an agricultural country where most of the population has a livelihood as farmers. As a form of contextual learning and alternative distance learning during the COVID-19 pandemic, teachers can take advantage of rice farming activities in Indonesia, known as rice Tandur (reverse planting), as physical science teaching materials. Therefore, this research aims to explore the concept of physical science contained in rice Tandur activities to be used for physical science learning. This research is descriptive research to describe the idea of physical science in rice planting activities. Data collection was conducted by documentation of rice planting activities as well as literature studies. After the documentation is collected, the analysis uses Kinovea software to find out the center of gravity (COG) and the corners formed by the limbs. Based on the results of analysis and literature studies, the concept of physics was obtained in the form of a third-class lever arm that can be used for science materials in high school classes. In addition, there is a center of gravity and torque concept in the torso's movement, which can be used as a material for learning physics in high school.